Factors Affecting the Success of Lean Construction Implementation in Indonesia - Moch Rian Silmi; Mohammad Arif Rohman (Journal of Civil Engineering, 2025)
The construction industry in Indonesia contributes significantly to the economy, but lags behind in technology adoption and faces environmental challenges. Lean Construction offers a solution by improving efficiency through waste reduction and value addition, although its application is still limited due to work culture resistance and low priority. This study aims to identify the factors that affect the success of lean implementation in East Java using SEM-PLS surveys and analysis. The results showed that organizational policies had a significant influence (46.2%), followed by teamwork (29.6%) and leadership (23.9%). Leadership is influenced by manpower and resources (71.1%), while organizational policies are influenced by optimization (88.7%). However, some variables, such as manpower vs. teamwork and optimization vs. leadership, don't have a significant influence. This study provides strategic insights to support the effective implementation of Lean Construction to improve the performance of the construction industry in Indonesia.